Use of recycled broken bricks as Partial Replacement Coarse Aggregate for the Manufacturing of Sustainable Concrete - Pinchi, S. (2020)
The bricks are one of the primary materials required for construction of homes that no used completely when executes all the walls due, the excess purchase, the cutting to be settle, the breaking for their transfer and its fixed dimensions; this situation requires monitoring on work site the order, cleanliness and accidents. A common practice is these bricks and/or waste are included in the clearing construction before being deposited or eliminated in dumps or sanitary landfills, with their early clogging and shortening them to ther design lifespan. An important alternative to reduce this waste, is to recycle them and reuse them as a concrete component material, due to their high absorption percentage that allows them to keep the water inside of them and then use it in the cement hydration process as internal curing of the concrete. In the present investigation, the effect of crushed clay brick as a replacement for coarse aggregate in concrete processing is studied. The results indicate that with 21 % replacement brick, the plastic contraction decreases, and the compressive strength and flexural strength increase.